2012
DOI: 10.1021/ie300882t
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extraction Process and Kinetics of Sterculia foetida Seed Oil and Its Process Augmentation for Biodiesel Production

Abstract: This article reports optimization and kinetic studies on extraction of Sterculia foetida seed oil and process optimization for biodiesel production from the same. The oil extraction follows first-order kinetics, and the yield was found to reach a maximum of 55.58 wt % for a 1:12 seed-to-hexane weight ratio. The activation energy and activation thermodynamic parameters at 338 K were determined as E a = 69.441 kJ mol −1 , ΔH ‡ = 66.63 kJ mol −1 , ΔS ‡ = −238.07 J mol −1 K −1 , and ΔG ‡ = 147.09 kJ mol −1 . Compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…When analyzing the first-order kinetics applied by Sivakumar et al (2012) to Sterculia foetida, the safflower oil extraction yield data obtained in this work could be represented up to 3600 s of extraction. At that time there was an important amount of oil remaining in the sample (4% and 8.5% at 7 and 9% of moisture content, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing the first-order kinetics applied by Sivakumar et al (2012) to Sterculia foetida, the safflower oil extraction yield data obtained in this work could be represented up to 3600 s of extraction. At that time there was an important amount of oil remaining in the sample (4% and 8.5% at 7 and 9% of moisture content, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found that first-order kinetics represented this process using Sterculia foetida seeds and algaes as raw material (Sivakumar et al, 2012;Suganya and Renganathan, 2012). The industrial process of safflower oil extraction in some plants of Argentina, similarly to what happens with sunflower, begins with the dehulling of the seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction temperature was found to have a considerable influence on the yield of biodiesel [40,41]. Thus, the experiments using the ferric-manganese doped sulfated zirconia solid catalyst were conducted at 120, 140, 160, 180, 200, 220°C.…”
Section: Temperature Of the Reactionmentioning
confidence: 99%
“…The reaction for which is positive and is negative reveals that the free energy of the final residue is higher than that of the initial compound, and all decomposition steps are non-spontaneous processes. On the other hand, the negative values of indicate more ordered activated complex than the corresponding reactants and that the reaction is slow [47]. The correlation coefficients of the Arrhenius plots of the thermal decomposition steps were found to lie in the range 0.97 to 0.…”
Section: Kinetic Data For the Macrocyclic Complexesmentioning
confidence: 96%